CD44 is a RAS/STAT5-regulated invasion receptor that triggers disease expansion in advanced mastocytosis - Müller, Niklas; Jawhar, Mohamad; Reiter, Andreas (Blood, 2018)
Abstract: The Hermes receptor CD44 is a multifunctional adhesion molecule that plays an essential role in the homing and invasion of neoplastic stem cells in various myeloid malignancies. Although mast cells (MCs) reportedly express CD44, little is known about the regulation and function of this receptor in neoplastic cells in systemic mastocytosis (SM). We found that clonal CD34+/CD38− stem cells, CD34+/CD38+ progenitor cells, and CD117++/CD34− MCs invariably express CD44 in patients with indolent SM (ISM), SM with an associated hematologic neoplasm, aggressive SM, and MC leukemia (MCL). In addition, all human MCL-like cell lines examined (HMC-1, ROSA, and MCPV-1) displayed cytoplasmic and cell-surface CD44. We also found that expression of CD44 in neoplastic MCs depends on RAS-MEK and STAT5 signaling and increases with the aggressiveness of SM. Correspondingly, higher levels of soluble CD44 were measured in the sera of patients with advanced SM compared with ISM or cutaneous mastocytosis and were found to correlate with overall and progression-free survival. To investigate the functional role of CD44, a xenotransplantation model was employed using severe combined immunodeficient (SCID) mice, HMC-1.2 cells, and a short hairpin RNA (shRNA) against CD44. In this model, the shRNA-mediated knockdown of CD44 resulted in reduced MC expansion and tumor formation and prolonged survival in SCID mice compared with HMC-1.2 cells transduced with control shRNA. Together, our data show that CD44 is a RAS-MEK/STAT5-driven MC invasion receptor that correlates with the aggressiveness of SM. Whether CD44 can serve as therapeutic target in advanced SM remains to be determined in forthcoming studies.